Aerobic bacterial profile and their antimicrobial sensitivity pattern in patients of otitis media with ear discharge - G.R., Jagannath Babu; S., Kavya; K., Anuradha (International Journal of Research in Medical Sciences, 2021)
Background: The average prevalence of Chronic suppurative otitis media (CSOM) in India is 5.2%. It is more prevalent due to various predisposing factors such as malnutrition, overcrowding, poor hygiene, inadequate health care, and recurrent upper respiratory tract infection. In recent years, there is increased preponderance of multi drug resistant organisms due to the irrational use of antibiotics, making treatment of CSOM more difficult. Methods: Samples from 100 subjects of uncomplicated CSOM who presented to the Oto-Rhino-Laryngology outpatient department of our hospital were collected. Aerobic bacterial profile and its Antimicrobial susceptibility were studied by conventional methods. Results were compiled and evaluated by descriptive statistics and inferential statistics. Results: Pseudomonas aeruginosa (50.7%) and Staphylococcus aureus (19.04%) were the predominant isolates in our study. Aminoglycosides and Fluoroquinolones were found to be effective first line drugs, followed by Carbapenems. Conclusions: These antibiotics can be used to prevent the life-long complications of CSOM. Timely culture and sensitivity helps in the management of these cases.